CENTRAL ASIA: UNIVERSAL DEMOCRACY,NATIONAL DEMOCRACY, OR ENLIGHTENED AUTHORITARIANISM? - TOLIPOV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2007)
The apologists of authoritarian regimes in the newly independent states have spent fifteen years of sovereign development creating and spreading the myth of so-called enlightened authoritarianism as the most desirable and implementable political model (principle) for these states. This conception has been surfacing more and more frequently in political discourse recent-ly. It looks like a product of the crisis that hit the political research of democratization issues in the post-Soviet (particularly Central Asian) countries.e can say very provisionally that the democratic rhetoric in the newly independent states has passed through three stages:(1) resolute statements about the democratic choice when these states gained their sovereignty.talk about the possibility of an exclu-sively national democratic model;acceptance of enlightened authoritari-anism as the most appropriate political system. These are mainly conceptual issues to be discussed from the conceptual point of view: the crisis in political research is caused by the domination of political short-term considerations and a politically motivated apology over the rigorous-ly scholarly and critical approach. Below I shall use the term “democratic constructionism” instead of the widely used concept “democratic construction” to separate the practical process of developing democracy as a political system from the theoretical process of creating an adapted concept of democracy.